Lung Function Impairment in Construction Workers – Influence of Smoking and Exposure Duration - Sasho, Stoleski; Jordan Minov; Dragan Mijakoski; Bislimovska, Dragana; Atanasovska, Aneta; Jovanka Karadzinska-Bislimovska (Scientific Foundation SPIROSKI, 2021)
AIM: The objective of the study was to assess the influence of exposure duration and smoking on ventilatory impairment among construction workers. METHODS: A cross-sectional study was performed, including 83 construction workers aged 18–64 years, compared to equivalent number of office controls matched by age, workplace exposure duration, and smoking status. Data on chronic respiratory symptoms, work history, and smoking status were collected by standardized questionnaire, while lung functional testing of the examined subjects was performed by spirometry. RESULTS: Mean values of spirometric parameters were lower in construction workers compared to controls with statistical significance registered for maximal expiratory flow (MEF25), MEF50, and MEF75. Lung functions of construction workers have been found to decrease in relation to exposure duration but reached significance only for small airways changes. There was a significant difference in detected ventilatory impairment between exposed workers and controls for any type of ventilatory impairment, as well as obstructive and combined ventilatory pattern and obstructive ventilatory pattern in small airways. Obstructive ventilatory impairment was significantly associated with life-time smoking in construction workers, while obstructive ventilatory pattern in small airways was significantly associated with life-time smoking. The combined effect of daily smoking, life-time smoking, and number of cigarettes smoked daily was shown to have a significant influence in their development. The risk for obstructive ventilatory pattern in small airways among exposed subjects was about 4 fold higher in those exposed more than 20 years (odds ratio [OR] = 3.68 [1.01–14.59] confidence interval [CI] 95%), and about 2.5 fold higher in smokers (OR = 2.57 [0.92-7.25] CI 95%). Exposure duration, smoking and age had independent effect only on small airways changes and force expiratory volume in the 1st s/force vital capacity %. CONCLUSION: Our data suggest the importance of the joint effect of job exposure in construction and daily smoking on the development of lung function impairment and airflow limitation, being dominant, especially on small airways.
Keywords: lung function; construction site; spirometry; smoking; job exposure